Neonatal mortality in the central districts of Ghana: analysis of community and composition factors - Adjei, G.; Darteh, E.K.M.; Nettey, O.E.A.; Doku, D.T. (BMC Public Health, 2021)
Background: Communities and their composition have an impact on neonatal mortality. However, considering the smallest health administrative units as communities and investigating the impact of these communities and their composition on neonatal mortality in Ghana have not been studied. Therefore, this study aimed to investigate the effect of community-, household- and individual-level factors on the risk of neonatal mortality in two districts in Ghana. Methods: This was a longitudinal study that used the Kintampo Health and Demographic Surveillance System as a platform to select 30,132 neonatal singletons with 634 deaths. Multilevel cox frailty model was used to examine the effect of community-, household- and individual-level factors on the risk of neonatal mortality. Results: Regarding individual-level factors, neonates born to mothers with previous adverse pregnancy (aHR = 1.38, 95% CI: 1.05–1.83), neonates whose mothers did not receive tetanus toxoid vaccine (aHR = 1.32, 95% CI: 1.08–1.60) and neonates of mothers with Middle, Junior High School or Junior Secondary School education (aHR = 1.30, 95% CI: 1.02–1.65) compared to mothers without formal education, had a higher risk of neonatal mortality. However, female neonates (aHR = 0.61, 95% CI: 0.51–0.73) and neonates whose mother had secondary education or higher (aHR = 0.37, 95% CI: 0.18–0.75) compared to those with no formal education had a lower risk of mortality. Neonates with longer gestation period (aHR = 0.95, 95% CI: 0.94–0.97) and those who were delivered at home (aHR = 0.56, 95% CI: 0.45–0.70), private maternity home (aHR = 0.45, 95% CI: 0.30–0.68) or health centre/clinic (aHR = 0.40, 95% CI: 0.26–0.60) compared to hospital delivery had lower risk of mortality. Regarding the household-level, neonates belonging to third quintile of the household wealth (aHR = 0.70, 95% CI: 0.52–0.94) and neonates belonging to households with crowded sleeping rooms (aHR = 0.91, 95% CI: 0.85–0.97) had lower risk of mortality. Conclusion: The findings of the study suggest the risk of neonatal mortality at the individual- and household-levels in the Kintampo Districts. Interventions and strategies should be tailored towards the high-risk groups identified in the study.
Research Article
Keywords: Neonatal mortality; Community-level factor; Household-level factor; Individual-level factor; Kintampo health and demographic surveillance system and frailty